2004
DOI: 10.1002/chin.200442198
|View full text |Cite
|
Sign up to set email alerts
|

A New Oxygenated Tricyclic Sesquiterpene from a Soft Coral of Nephthea Species of Andaman and Nicobar Coasts of Indian Ocean.

Abstract: From the ethanol extract of the title coral the novel compound (I) together with a known substance is isolated. -(RAO, C. B.; SEKHAR, V. C.; SARVANI, B.; RAO*, D. V.; Indian J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The compounds 1 and 2 were trans and cis isomers, but downfield shifts were observed at H-1β in 1 and 2 , and H-10β in 2 . The downfield shifts of both cyclopropane methines for 2 (δH 1.45 and 1.38) were similar to those observed in cyclocolorenone (δH 1.54 and 1.29) and its derivative [13,14]. It is reported that this cyclocolorenone also has one double bond beside these cyclopropane methines similar to those of 1 and 2 , where the double bond was located at C2/C3.…”
Section: Resultssupporting
confidence: 71%
“…The compounds 1 and 2 were trans and cis isomers, but downfield shifts were observed at H-1β in 1 and 2 , and H-10β in 2 . The downfield shifts of both cyclopropane methines for 2 (δH 1.45 and 1.38) were similar to those observed in cyclocolorenone (δH 1.54 and 1.29) and its derivative [13,14]. It is reported that this cyclocolorenone also has one double bond beside these cyclopropane methines similar to those of 1 and 2 , where the double bond was located at C2/C3.…”
Section: Resultssupporting
confidence: 71%
“…This tricyclic sesquiterpene was earlier isolated from different members of the genus Nephthea, eg, N. chabrolii AUDOIN. 72 Additionally, another nardosinane sesquiterpene with the molecular formula C 15 H 22 O 2 , in good agreement with the mass ion peak at m/z 233.154, was characterized as lemnalactone (4). This compound was firstly identified from the soft coral Paralemnalia digitiformis Macfadyen.…”
Section: Ftir Characterization Of the Synthesized Snpsmentioning
confidence: 54%
“…The structures of 1-3 were elucidated by spectroscopic methods including 1D and 2D NMR, and ESI-MS, together with comparison with those previously reported in the literature. On the other hand, the oxygenated tricyclic sesquiterpene, cyclocolorenone (1) has been isolated so far from terrestrial liverworts [13][14][15], terrestrial plants [16,17], and the soft coral Nephthea species [18,19]. This is the first time that the isolation of (+)-cyclocolorenone (1) has been reported from marine algae.…”
Section: Present Studymentioning
confidence: 95%